Hematological Profile and Spleen Histology Improvement in Diabetic Rats Treated with PLGA Nanoparticles-Ethanol Extract of Jengkol (Archidendron pauciflorum) Fruit Peel - Malini, Desak Made (Biotropika: Journal of Tropical Biology, 2022)
Jengkol (Archidendron pauciflorum) fruit peel-ethanol extract (JFP) contains several chemical compounds that act as antioxidant agents and are considered to have the potential to treat chronic disorders such as diabetes mellitus. Plant extract is generally applied in polylactic-co-glycolic acid (PLGA) nanoparticles due to its efficiency in entering the target organs. This study aims to investigate the effect of PLGA nanoparticles-ethanol extract of jengkol fruit peel (PLGA nanoparticle-JFP) on improving the hematological profile and the spleen histology of streptozotocin-induced diabetic rats. The treatment group was divided into six groups: (1) control group, (2) streptozotocin control (STZ); (3) 10 mg/kg BW of glibenclamide (GLB); (4) 770 mg/kg BW of jengkol fruit peel-ethanol extract (JFP1); (5) 110 mg/kg BW of JFP (JFP2); and (6) 770 mg/kg BW PLGA nanoparticle-JFP (PLGA-JFP). PLGA-JFP group showed a significant increase in erythrocytes and leukocytes counts (7.73x106 ± 0.02 cell/mm3 and 9.68x103 ± 3.0 cell/mm3 respectively), a decrease in lymphocytes and neutrophils percentage (66.5%±0.5% and 28±1.4% respectively) compared to the STZ group, and no significant difference in monocyte, eosinophils, and basophils percentage within groups. On the spleen histology, the white pulp diameter and the red pulp area showed significantly smaller (168.31±10.69μm and 8,01.28± 480.33 μm2 respectively) compared to the STZ group. Almost all parameters showed no significant difference compared to the GLB group but are significantly different from the control group. The administration of PLGA nanoparticle-JFP was proven to reverse hematological parameters and improve the spleen histology but has not yet reversed the diabetic rats’ condition back to normal.